Conceptualizing university-industry linkages in resource-constrained environments. (1st September 2018) - Datta, Surja; Souleh, Samah
This article problematizes the conventional models of U-I linkages by pointing to the fact that they assume a resource-abundant context in which research funding is not a constraint. While such an assumption generally holds true in developed countries it is unlikely to be the case in the context of developing nations. Paucity of research funding leads to a situation where universities possess few formal intellectual properties such as patents and copyrights. The conventional U-I linkages that are predicated on explicit knowledge are therefore generally absent in developing countries. The article argues that it is possible for universities to develop productive linkages with the industry even in resource-constrained environments (RCE) by leveraging their human capital and knowledge assimilation and dissemination capabilities. The article presents several case illustrations drawn from the higher education sector in India. The Indian case suggests that while conventional university–industry (U-I) linkages are not prevalent in the country, there are other forms of university and industry collaborations that have been largely ignored in the extant literature.